Increased nasality of connected speech in patients underwent modified Lothrop procedure for refractory chronic rhinosinusitis: Cross-sectional and prospective study. Issue 12 (24th August 2022) - Pan, Yi-An; Wang, Ying-Piao; Lee, Guo-She; Hsieh, Li-Chun; Chen, Yi-Chen
Abstract : Background: The endoscopic modified Lothrop procedure (EMLP) is performed to create a large frontal neostium in patients who had failed previous frontal sinus surgeries. EMLP causes obvious changes in the volume and anatomy of the sinuses, which may cause a more significant change in nasality. This study aimed to evaluate the changes in nasalance in patients who underwent EMLP by comparing their preoperative nasalance to the established normative values and postoperative nasalance. Methods: This was a prospective study. Twenty-one patients diagnosed with refractory frontal sinusitis who were indicated to undergo EMLP were enrolled. One hundred one healthy participants were enrolled as norm references. The Nasometer II Model 6400 (KayPENTAX) was used to analyze the nasalance scores. Nasalance scores were tested before surgery and 1 and 3 months after the surgery. Results: The normative references of nasalance were (mean ± SD) 14.6% ± 6.7%, 39.4% ± 8.4%, and 55.8% ± 8.3% for the oral passage, oral-nasal passage, and nasal sentences, respectively. The mean nasalance scores pre-EMLP and 1 and 3 months post-EMLP were 23.2% ± 9.6%, 29.0% ± 9.3%, and 29.9% ± 0.4% for the oral passage; 48.7% ± 10.7%, 54.7% ± 7.7%, and 56.4% ± 7.2% for the oral-nasal passage; and 62.7% ± 10.9%, 69.8% ± 6.7%, and 70.7% ± 6.4% for the nasal sentences, respectively. Compared with the normative references, pre-EMLP nasalance was higher for all the three speech stimuli (t-test, p < 0.05). Post-EMLP nasalance also significantly increased for all the three stimuli at the 1- and 3-month follow-up visits (Paired t-test, p < 0.05). Conclusion: EMLP has a short-term impact on resonance; however, long-term follow-up is required for further study.